Drug Discovery and Development Targeting Dementia - Agnieszka Zagórska; Anna Czopek; Monika Fryc; Anna Jaromin; Ben J. Boyd (MDPI AG, 2023)
Dementia, most often associated with neurodegenerative diseases, affects millions of people worldwide, predominantly the elderly. Unfortunately, no treatment is still available. Therefore, there is an urgent need to address this situation. This review presents the state of the art of drug discovery and developments in targeting dementia. Several approaches are discussed, such as drug repurposing, the use of small molecules, and phosphodiesterase inhibitors. Furthermore, the review also provides insights into clinical trials of these molecules. Emphasis has been placed on small molecules and multi-target-directed ligands, as well as disease-modifying therapies. Finally, attention is drawn to the possibilities of applications of nanotechnology in managing dementia.